Dental erosion: causes, diagnostics and treatment. - Cecilia Sosa-Puente; Juan Solís-Soto; Norma Cruz-Fierro; Sonia López-Villarreal; Sergio Nakagoshi-Cepeda (Universidad de Concepción., 2014)
Despite being a commonly studied topic, it is difficult to find studies which explain the problem of dental erosion. For this article, literature was analyzed to find information on the agents which trigger dental erosion, the main diagnosis methods, the most common treatments used nowadays and the interrelationship with dental materials. The etiology of dental erosion is multifactorial, including acids, eating disorders and gastro-esophageal reflux. However, biological factors such as saliva or habits also play a part in the establishment of this condition. In order to establish a reliable diagnosis, clinical appearance becomes decisive. The Basic Index Erosive Wear Examination (BEWE), created in 2008, is an auxiliary diagnosis tool for assessing the status and progress of the erosion. Treatment should be linked to the eradication of the causative agent and it can range from simple observational monitoring of slightly affected teeth to the placement of total crowns in the most severe cases, but this will depend entirely on the extent, severity, symptoms and type of dentition. Regarding dental materials used in the treatment of eroded parts, there are glass ionomer and composite; the latter presents the greatest resistance to biodegradation when interacting with acids. Glass ionomers are the most vulnerable material while resin is seen as the most resistant. In conclusion, dental erosion has become an issue of great importance in the dental practice because of its serious impact on dental structures. Consequently, it is ranked among the most important dental disorders in the present day.